Steps Toward Engagement Integrity: Learning From Participatory Visual Methods in Marginalized South African Communities - Black, Gillian F.; Sykes, Pam (Frontiers in Public Health, 2022)
Community engagement and involvement has been increasingly recognized as an ethical and valuable component of health science research over the past two decades. Progress in the engagement field has been accompanied by emerging standards that emphasise participation, two-way communication, inclusion, empowerment, and ownership. Although these are important and noble benchmarks, they can represent a challenge for research conducted in marginalized contexts. This community case study reports on the methods, outcomes, constraints and learning from a community engagement project called Bucket Loads of Health, implemented in the Western Cape province of South Africa. The project approach involved using multiple participatory visual methods to foster two-way communication between members of two disenfranchised communities, Enkanini and Delft, and a group of water microbiologists at Stellenbosch University who were conducting research in Enkanini. The project was carried out during the 2018 Western Cape water crisis, under the growing threat of ‘Day Zero’. The resulting visual outputs illustrated the negative impacts of water shortage on health and wellbeing in these community settings and showcased scientific endeavours seeking to address them. Engagement included knowledge exchange combining body maps, role play performances and films created by the community members, with hand maps, posters and presentations produced by the scientists. Whereas these engagement tools enabled reciprocal listening between all groups, their ability to respond to the issues raised was hindered by constraints in resources and capacity beyond their control. An additional core objective of the project was to bring the impacts of water shortage in participating communities, and the work of the research team, to the attention of local government. The case study demonstrates the challenges that politically ambitious community engagement faces in being acknowledged by government representatives. We further the argument that research institutions and funders need to match professed commitments to engagement with training and resources to support researchers and community members in responding to the needs and aspirations surfaced through engagement processes. We introduce the concept of engagement integrity to capture the gap between recommended standards of community engagement and what is realistically achievable in projects that are constrained by funding, time, and political interest.